A percepção dos médicos residentes em relação a presença de distúrbios do sono e o impacto na qualidade de vida - Silva, Darley Paulo Fernandes da (2018)
Introduction: Medical residency is the most suitable model for the physician to specialize through the practice with the supervision of more experienced professionals. However, when medical residency offers inadequate working conditions, it can cause harm to the work and safety of resident physicians and their own patients. Among these problems we can mention sleep disturbances by the shift regime.Objectives: To evaluate the impact of hypersomnolence and quality of life in resident physicians and to evaluate the association between hypersensitivity and sociodemographic characteristics. Material and Methods: Nine hundred resident physicians were interviewed enrolled in the medical residency program of the São José do Rio Preto Base Hospital. The subjects answered a questionnaire containing instruments for assessing sleep, quality of life and risk of depression. Sleep assessment was performed using the Epworth Daytime Sleepiness Scale, a self-administered questionnaire to assess hypersensitivity. Quality of life was assessed through the Medical Outcomes Study 36, a 36-item multidimensional questionnaire and the risk of depression was studied through the Self-Reporting Questionnaire (SRQ-20) developed by the World Health Organization. Results: Sociodemographic variables do not seem to influence the hypersomnolence of resident physicians. In relation to the quality of life scales, the risk of depression and functional capacity were not correlated with hypersomnolence, while the variables variables of general health status, vitality, social aspects and pain domain were predictors of somnolence. We observed that hypersomnolence interferes in the residents' quality of life, so that for all SF-36 domains, the mean score is lower for the hypersolent. Conclusions: There is a correlation between hypersomnolence and quality of life and that hypersomnia is a significant predictor for the perception of the quality of life of resident physicians. The sociodemographic characteristics do not seem to influence the sleep quality of these physicians